Drug concentration at the site of disease in children with pulmonary tuberculosis. (25th April 2022) - Lopez-Varela, Elisa; Abulfathi, Ahmed A.; Strydom, Natasha; Goussard, Pierre; van Wyk, Abraham C.; Demers, Anne Marie; Deventer, Anneen Van; Garcia-Prats, Anthony J.; van der Merwe, Johannes; Zimmerman, Matthew; Carter, Claire L.; Janson, Jacques; et al.
Abstract: Background: Current TB treatment for children is not optimized to provide adequate drug levels in TB lesions. Dose optimization of first-line antituberculosis drugs to increase exposure at the site of disease could facilitate more optimal treatment and future treatment-shortening strategies across the disease spectrum in children with pulmonary TB. Objectives: To determine the concentrations of first-line antituberculosis drugs at the site of disease in children with intrathoracic TB. Methods: We quantified drug concentrations in tissue samples from 13 children, median age 8.6 months, with complicated forms of pulmonary TB requiring bronchoscopy or transthoracic surgical lymph node decompression in a tertiary hospital in Cape Town, South Africa. Pharmacokinetic models were used to describe drug penetration characteristics and to simulate concentration profiles for bronchoalveolar lavage, homogenized lymph nodes, and cellular and necrotic lymph node lesions. Results: Isoniazid, rifampicin and pyrazinamide showed lower penetration in most lymph node areas compared with plasma, while ethambutol accumulated in tissue. None of the drugs studied was able to reach target concentration in necrotic lesions. Conclusions: Despite similar penetration characteristics compared with adults, low plasma exposures in children led to low site of disease exposures for all drugs except for isoniazid.